Aorto-mitral curtain reconstruction in invasive double-valve endocarditis: mid-term outcomes - Vobornik, Martin; Timbilla, Salifu; Gofus, Jan; Smolak, Petr; Chek, James Lago; Pojar, Marek; Cermakova, Eva; Zacek, Pavel; Vojacek, Jan (Frontiers in Cardiovascular Medicine, 2023)
Background Invasive double-valve endocarditis with structural damage (abscess or perforation) of the aorto-mitral curtain is a relatively rare but fatal diagnosis requiring complex surgical reconstruction. This study presents the short-term and mid-term outcomes from a single center. Methods From 2014 to 2021, 20 patients with double-valve endocarditis with structural damage of the aorto-mitral curtain underwent surgical reconstruction (Hemi-Commando procedure n = 16 and Commando procedure n = 4). Data were obtained retrospectively. Results In 13 cases, the procedure was a reoperation. The mean cardiopulmonary bypass time was 239 ± 47 min and the mean cross-clamp time was 186 ± 32 min. Concomitant procedures were tricuspid valve repair in two, coronary revascularization in one, closure of a ventricular septal defect in one and hemiarch (using circulatory arrest) in one patient. Eleven patients (55%) required surgical revision for bleeding. Thirty-day mortality was 30% (6 patients)—3 patients from the Hemi-Commando group (19%) and 3 patients from the Commando group (75%). Overall survival at 1, 3 and 5 years was 60%, 50% and 45% respectively. Reoperation was required by 4 patients. Freedom from reoperation at 1, 3 and 5 years was 86%, 71% and 71% respectively. Conclusion Despite the high postoperative morbidity and mortality, complex surgical reconstruction of the aorto-mitral continuity of patients with double-valve endocarditis represents the only real chance for survival. Mid-term outcomes are acceptable, but strict follow-up is required due to the risk of valve failure.